The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1126/science.1079641
|View full text |Cite
|
Sign up to set email alerts
|

Role of EphA4 and EphrinB3 in Local Neuronal Circuits That Control Walking

Abstract: Local circuits in the spinal cord that generate locomotion are termed central pattern generators (CPGs). These provide coordinated bilateral control over the normal limb alternation that underlies walking. The molecules that organize the mammalian CPG are unknown. Isolated spinal cords from mice lacking either the EphA4 receptor or its ligand ephrinB3 have lost left-right limb alternation and instead exhibit synchrony. We identified EphA4-positive neurons as an excitatory component of the locomotor CPG. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
298
5
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(332 citation statements)
references
References 24 publications
27
298
5
2
Order By: Relevance
“…Although, in this article, EphA4 was not discussed in association with ephrin-B3, there are some previous reports about the interaction between ephrin-B3 and EphA4 (38,39). In summary, these studies provide the evidence that EphrinB3/EphA4 has an important role in neuronal circuit formation, growth, and development.…”
Section: Discussionmentioning
confidence: 81%
“…Although, in this article, EphA4 was not discussed in association with ephrin-B3, there are some previous reports about the interaction between ephrin-B3 and EphA4 (38,39). In summary, these studies provide the evidence that EphrinB3/EphA4 has an important role in neuronal circuit formation, growth, and development.…”
Section: Discussionmentioning
confidence: 81%
“…Previously, we have shown that the abnormal adult hopping gait in ephA4-KO mice can be elicited in the isolated neonatal spinal cord preparation, suggesting that intrinsic defects in the spinal cord locomotor CPG underlie this phenotype (16). In the isolated spinal cord, the abnormal hopping gait was seen as synchrony between bilaterally located, lumbar segment 2 (L2) predominantly flexor motor neurons as well as synchrony between caudally located, predominantly extensor L5 motor neurons.…”
Section: Resultsmentioning
confidence: 94%
“…1C), because the iL2 ventral root activity always showed strict alternation with that of the iL5 in all preparations (WT, heterozygote, and homozygote; also see ref. 16). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective expression of a genetic tool in the glutamatergic neurons in hindbrain and spinal cord has been achieved by inserting a transgene under the control of vesicular glutamate transporter 2 (Vglut2) promoter [18]. Vglut2 is the dominant glutamate transporter expressed by in these regions [22,23]. In this transgenic mouse, the genetic tool was found only in Vglut2-positive neurons in the central nervous system and exclusively activated by photostimulation.…”
Section: Genetic Identitymentioning
confidence: 99%